Intraocular lens power calculation in keratoconus; A review of literature - Leila Ghiasian; Navid Abolfathzadeh; Navid Manafi; Ali Hadavandkhani (Journal of Current Ophthalmology, 2019)
Purpose: To review the published literature regarding cataract surgery in keratoconus (KCN) patients with emphasis on challenges encountered during intraocular lens (IOL) power calculation and their solutions. Methods: A literature review was performed to investigate all the relevant articles on the advancements of IOL calculations in KCN patients. Results: Cataract surgery in keratoconic eyes can improve patients' refraction, and proper patient selection and IOL calculation methods are necessary to get the best results. The main problem in KCN patients is unreliable biometric measurements. It is more difficult to make conclusions in more advanced keratoconic corneas, as the steep keratometric values in these eyes will result in the selection of a low-power IOL. Presence of a low-power IOL will yield in extreme postoperative hyperopia, and IOL exchange might be mandatory. In cases in which keratoplasty may be needed in the future, contact lens fitting can help surgeons make a better decision preoperatively. Axial length (AL) measurements may have better repeatability and reproducibility than keratometry (K) readings in keratoconic eyes. SRK II formula may provide the most accurate IOL power in mild KCN. There is still not a comprehensive consensus of which formula is the best one in moderate and severe KCN, as the literature is limited in this subject. Conclusions: Various methods of IOL power calculation optimization and recommendations may hold the key to improve surgical outcomes in keratoconic eyes. There are multiple sources of biometric error in KCN patients, hence IOL calculation methods may not be as efficient as expected in these eyes. Keywords: Intraocular lens power, Cataract, Keratoconus, Keratoconic, Corneal ectasia